SDN 기반 산업제어시스템 제어명령 판별 메커니즘 - 조민정(Minjeong Cho); 석병진(Byoungjin Seok); 김역(Yeog Kim); 이창훈(Changhoon Lee) (디지털콘텐츠학회논문지, 2018)
산업제어시스템(ICS, Industrial Control System)은 산업 분야 제어 공정에 대한 감시와 제어를 수행하는 시스템을 말하며 수도, 전력, 가스 등 기반시설에서 응용되고 있다. 최근 ICS에 대해 Brutal Kangaroo, Emotional Simian, stuxnet 3.0 등 사이버공격이 지속적으로 증가하고 있고 이와 같은 보안위험은 인명피해나 막대한 금전적 손실을 초래한다. ICS에 대한 공격 방법 중 제어계층에 대한 공격은 제어명령을 조작해 현장장치계층의 장치를 오작동하게 하는 것이다. 따라서, 본 논문에서는 이에 대한 대응으로 산업제어시스템에서 제어계층과 현장장치 계층사이에 SDN을 적용해서 제어명령의 정상 여부를 판별하는 메커니즘을 제안하고 가상의 제어시스템을 구성해 시뮬레이션 결과를 소개한다. Industrial Control System (ICS) is a system that carry out monitoring and controls of industrial control process and is applied in infrastructure such as water, power, and gas. Recently, cyber attacks such as Brutal Kangaroo, Emotional Simian, and Stuxnet 3.0 have been continuously increasing in ICS, and these security risks cause damage of human life and massive financial losses. Attacks on the control layer among the attack methods for ICS can malfunction devices of the field device layer by manipulating control commands. Therefore, in this paper, we propose a mechanism that apply the SDN between the control layer and the field device layer in the industrial control system and to determine whether the control command is legitimate or not and we show simulation results on a simply composed control system. KCI Citation Count: 0